2016
DOI: 10.20527/jwem.v4i2.54
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting of Kerangas Forest as Natural Medicine Material Sources: Screening Phytochemistry Compound of Kerangas Forest Tree Species

Abstract: <!--[if gte mso 9]><xml> <w:WordDocument> <w:View>Normal</w:View> <w:Zoom>0</w:Zoom> <w:TrackMoves/> <w:TrackFormatting/> <w:PunctuationKerning/> <w:ValidateAgainstSchemas/> <w:SaveIfXMLInvalid>false</w:SaveIfXMLInvalid> <w:IgnoreMixedContent>false</w:IgnoreMixedContent> <w:AlwaysShowPlaceholderText>false</w:AlwaysShowPlaceholderText&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
1
0
1
Order By: Relevance
“…The phytochemistry of dried leaves and barks of selected trees from the Kerangas forest was investigated. The findings revealed that numerous phytochemistry substances are present in portions of selected trees from the Kerangas forest which is in line with the study conducted by Kissinger et al (2016). The methanol extract of tree species from Kerangas forest can obtain many potential bioactivities (Abbasi et al 2009;Abera 2014).…”
Section: Medicinal Plants Based On the Plant Part Usedsupporting
confidence: 80%
See 1 more Smart Citation
“…The phytochemistry of dried leaves and barks of selected trees from the Kerangas forest was investigated. The findings revealed that numerous phytochemistry substances are present in portions of selected trees from the Kerangas forest which is in line with the study conducted by Kissinger et al (2016). The methanol extract of tree species from Kerangas forest can obtain many potential bioactivities (Abbasi et al 2009;Abera 2014).…”
Section: Medicinal Plants Based On the Plant Part Usedsupporting
confidence: 80%
“…The results of our study showed that there were 42 plants found in the heath forest, 38 of which were utilized as medicine by the people (90.48 %). Analgesic, antibacterial, antidiabetic, anti-plasmodium, and vitality are among the advantages obtained from the ten species in our study (Kissinger et al 2016).…”
Section: Composition Of Medicinal Plants By Familymentioning
confidence: 76%
“…Tanaman pelawan yang merupakan anggota dari genus Tristaniopsis dengan famili Myrtaceae ini merupakan salah satu tumbuhan yang digunakan oleh masyarakat Bangka sebagai obat tradisional untuk mengobati berbagai penyakit, seperti radang lambung, diabetes melitus, sakit perut, kerusakan pada hati, selain itu dapat digunakan juga sebagai peningkat stamina dan sebagai antioksidan. Hampir semua bagian tanaman pelawan dapat digunakan seperti daun, kulit kayu, akar dan air dari batang (Kissinger et al, 2013); (Kissinger et al, 2016).…”
Section: Aunclassified